2019
DOI: 10.1155/2019/3281260
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress of Research on Neurodegenerative Diseases of Salvianolic Acid B

Abstract: Salvia miltiorrhiza Bunge (Lamiaceae), one of the most commonly used traditional Chinese herbs, is widely used for the treatment of cardiovascular disease, cerebrovascular disease, Alzheimer’s disease, and Parkinson’s disease in clinical practice. Salvianolic acid B (Sal B, C36H30O16, FW=718.62) is the main water-soluble active ingredient of Salvia miltiorrhiza Bunge, which performs prophylactic and therapeutic activities against neurodegenerative diseases. So far, numerous studies have proved that multiple fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…To improve the efficacy of HLJDD, we excluded Radix Scutellariae from the HLJDD. According to our clinical practice, we further added Salvia miltiorrhiza, Curcuma longa L., and Acorus tatarinowii, which are beneficial to A β peptide clearance in the animal model [20, 8183]. Thus, we generated our newly modified formula of HLJDD, which is HLJDD without Radix Scutellariae, and with the addition of Salvia miltiorrhiza, Curcuma longa L., and Acorus tatarinowii.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the efficacy of HLJDD, we excluded Radix Scutellariae from the HLJDD. According to our clinical practice, we further added Salvia miltiorrhiza, Curcuma longa L., and Acorus tatarinowii, which are beneficial to A β peptide clearance in the animal model [20, 8183]. Thus, we generated our newly modified formula of HLJDD, which is HLJDD without Radix Scutellariae, and with the addition of Salvia miltiorrhiza, Curcuma longa L., and Acorus tatarinowii.…”
Section: Discussionmentioning
confidence: 99%
“…About 1000 species belong to this genus and they are herbaceous, suffruticosus or shrubby perennial plants displaying a remarkable diversity in growth forms, in floral morphology and pollination biology, and in secondary metabolites production [ 20 ]. The chemical composition of Salvia species is particularly rich in sesquiterpenoids, diterpenoids, triterpenoids, steroids, polyphenols and others [ 21 , 22 ], and bioactive molecules were reported to exert proapototic and anticancer activities, to act in prevention and treatment of cardiovascular diseases, to be therapeutic in liver diseases, to be active in the central nervous system as a potential cognitive protective, and to prevent or disaggregate beta amyloid and fibrils as inhibitors of acetylcholinesterase [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 showed that the results of three independent experiments yielding excellent assay metrics (four in the six of the Z’ factors were above 0.5), indicating a reliable platform. Both Res and Sal B are shown to targeting multiple signaling pathways, [24–27] including autophagy, [28,29] a mechanism relates to amyloid scavenging. Therefore, both of them had complicated molecular inhibitory effects on hIAPP amyloid formation, leading to the Z′ factor less than 0.5.…”
Section: Resultsmentioning
confidence: 99%